Serumpun international academic symposium (saas 2023) programme: its effectiveness and role in enhancing UiTM Pahang’s international - Hashim, Hasnizawati; Abdul Aziz, Roslina; Abd. Aziz, Mohd. Norafizal; Asmui, Mas’udah; Ramli, Nazirah (GADING Journal for the Social Sciences, 2025)
To bolster UiTM’s pursuit of “Globally Renowned University” status by 2025, UiTM Pahang initiated Serumpun International Academic Symposium (SAAS 2023), a collaborative effort between UiTM Pahang, Universitas Hasanuddin (UnHas), and Universitas Muhammadiyah Purworejo (UMP), Indonesia with the aim of supporting UiTM's international agenda (PI007, PI008, PI009, PI010, PI084) and fostering closer ties with industry partners and UiTM Pahang alumni (PI080). In achieving these objectives, SAAS 2023 orchestrated a series of five international activities conducted via the Webex platform, involving a wide range of participants, including students, academics, alumni, and industrial players. A total of 139 respondents took part in the study. A survey using Google Forms was administered to measure the programme's effectiveness. Descriptive statistics was applied to obtain the findings. The findings indicated an overall satisfaction with the programme content and its clear objectives. The programme was also highly valued for its impact on attitude strengthening, self-development, continuous learning, and relevance to students' studies. It is concluded that SAAS 2023 is a testament to the potential of academic collaborations in fostering positive change, creating meaningful and strategic global collaboration, and strengthening industrial and alumni partnerships in higher education.